2014
DOI: 10.1155/2014/898361
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effects of Curcumin on Serum Cytokines in Obese Individuals: A Randomized Controlled Trial

Abstract: Background. Obesity is a disorder often accompanied by a heightened state of systemic inflammation and immunoactivation. The present randomized crossover trial aimed to investigate the efficacy of curcumin, a bioactive polyphenol with established anti-inflammatory and immunomodulatory effects, on the serum levels of a panel of cytokines and mediators in obese individuals. Methods. Thirty obese individuals were randomized to receive curcumin at a daily dose of 1 g or a matched placebo for 4 weeks. Following a 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 184 publications
(119 citation statements)
references
References 43 publications
4
112
0
3
Order By: Relevance
“…Literature review showed curcumin attracted increasing attention for the treatment of a range of conditions because of its numerous health benefits and people consuming curcumin in daily life have better health status [6,7,[36][37][38][39]. Due to side effects of chemical drugs, except in severe cases, chemical drugs consumption is not recommended for treating PMS.…”
Section: Discussionmentioning
confidence: 99%
“…Literature review showed curcumin attracted increasing attention for the treatment of a range of conditions because of its numerous health benefits and people consuming curcumin in daily life have better health status [6,7,[36][37][38][39]. Due to side effects of chemical drugs, except in severe cases, chemical drugs consumption is not recommended for treating PMS.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds act as ROS scavengers, Nrf2 activators or both. Nrf2 activators have shown better results than direct antioxidants [123][124][125][126][127][128][129][130][131][132][133][134].…”
Section: Clinical Trials Using Natural Nrf2 Activatorsmentioning
confidence: 99%
“…Curcumin has been assessed in the treatment of obesity [123,124], metabolic syndrome [125] and prediabetes [126]. Oral consumption is effective lowering serum triglyceride, interleukin-1 , interleukin-4, vascular endothelial growth factor, insulin resistance index (HOMA-IR) and increasing adiponectin.…”
Section: Clinical Trials Using Natural Nrf2 Activatorsmentioning
confidence: 99%
“…Later, an intervention was carried out with the same type and dose of curcumin in non‐diabetic obese individuals who had either at least two risk factors for coronary heart disease (CHD) (BMI > 30 and LDL: 160–190 mg/dL) or ≥ 2 CHD risk factors and LDL: 130–160 mg/dL. In this study, curcumin decreased IL‐1β, IL‐4, and the vascular endothelial grow factor (VEGF) in serum without changes in the interleukins IL‐1, IL‐2, IL‐6, IL‐8, IL‐10, the interferon gamma (IFNγ), epidermal growth factor (EGF), monocyte chemoattractant protein 1 (MCP‐1), and TNF‐α levels . It is important to note that these findings do not exclude a potential tissue‐specific anti‐inflammatory effect of curcumin.…”
Section: Clinical Trials Using Curcumin To Improve Ir and Ir‐associatmentioning
confidence: 87%